USING PODCAST TO IMPROVE STUDENTS’ LISTENING SKILL IN LEARNING ENGLISH - Siti Latifatul Rosidah (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This research is about increasing students’ listening skill ability by using podcast as one of material sources taken from internet. The objective of this study is to describe the improvement of students’ listening ability using podcast in their learning. This research is an Action Research which is supported by planning, action, observation and reflection in two cycles. The participants are the students of English regular class at the second semester of Faculty of Economics and Business University of Muhammadiyah Jakarta. The data collection technique uses quantitative and qualitative data. The qualitative data are obtained from the result of observation, interview, and questionnaire done by teacher and collaborator teacher. Meanwhile, the quantitative data are taken from pre-test and post-test. The result is then analyzed using descriptive statistics to know the difference of scores before and after the implementation of podcast. The result shows that podcast can improve students’ listening skill and it is an effective tool to be applied to listening classes to encourage students' interest in listening activity. It can be seen from the average of result of their pre-test, post-test I dan post-test II that significantly increased. In addition, the result of observation shows that students’ interest and enthusiasm during learning activity improved significantly.